Pengaruh Perkembangan Teknologi Terhadap Terjadinya Kejahatan Mayantara (Cybercrime) - Raodia Raodia (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2019)
Abstractsimply influence of perkembagan of technology to the happening of badness of or mayantara of cybercrime that is new badness appearance which exploit growth of technology. Badness also more and more to expand and vary. But morely special causing growth of wrong technology use to [do/conduct] badness that is 1. Accessing internet which is not limited 2. small risk, where by exploiting internet to [do/conduct] badness, deed which they [do/conduct] will very [is] difficult known or traced, because nature of global internet so that they feel safe in [doing/conducting] badness 3. weak Security network system, security system in so many network of internet in Indonesia tend to still weaken, so that its security system [is] easy to penetrated by [all] perpetrator of cybercrime which (it) is true have the expert in that thing is. As for way of prevention and penanggulangan of badness of or mayantara of cybercrime that is 1. Make-Up of the quality of human resource in police institution and of aparatur enforcer of law 2. Making special [code/law] or regulation for the badness of or mayantara of cybercrime. 3.Meningkatkan computer network security system.